Small state regional cooperation, South-South and South-North migration, and international trade - Maurice Schiff (Institute for the Study of Labor (IZA), 2010)
This paper provides a different basis than previous analyses for regional bloc formation and regional migration. Due to low bargaining power and fixed costs, small states face a severe disadvantage in negotiations with the rest of the world and might benefit by forming a regional bloc. The study a) presents a general equilibrium model where bargaining power, international (IC) and regional (RC) negotiation costs, number of issues negotiated (N), and accession rule to the bloc determine its size and welfare impact, and b) examines the impact of international migration as well as the migration-trade relationship. The main findings are: i) the likelihood of regional bloc formation, its size and welfare impact increases with IC, N and decreases with RC; ii) bloc size is optimal (below the optimum) if an accession fee is (is not) charged; iii) South-South migration raises bloc size and welfare; iv) South-South migration and trade are complements under market access negotiations and are substitutes under negotiations for unilateral transfers as well as under migrant remittances; and vi) South-North migration and bloc formation, and South-North and South-South migration, are substitutes for the states that benefit from membership in the bloc.
Keywords: F15; F16; F22; 330; Small states; regional cooperation; South-South migration; South-North migration; trade; Kleinstaat; Internationale Zusammenarbeit; Handelsblock; Verhandlungsmacht; Wohlfahrtseffekt; Internationale Wanderung; Außenwirtschaft; Süd-Süd-Beziehungen; Nord-Süd-Beziehungen; Allgemeines Gleichgewicht; Theorie